The donation of the library of the archbishop Bartolomé María de las Heras (1805-1823) to the Santo Toribio Seminary, on the eve of the Independence of Peru - Benito, José Antonio (Mercurio Peruano, 2018)
José Agustín Puente Candamo announced in 1955 a piece of news about the library of Bartolomé María de las Heras. A second inventory is offered here in 1816 -for its donation to the Santo Toribio Seminary-, which highlights the singular career of Monsignor Bartolomé María de las Heras, who was the last prelate of Lima during Viceroyalty and the first of the Independence, in decisive years in the country’s history and that the prelate lives with prudence and responsibility. One of the means to approach the sources which fed his thought is provided by his personal library, which presents numerous works of theology, law and other readings, among them a copy of the first editions of Don Quixote, which is still preserved in the historical library of the Seminary, now under the aegis of the School of Ecclesiastical and Civil Theology of Lima.